Mexico : Detailed Assessment Report on Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2009)
This paper presents Mexico's detailed assessment report on antimoney laundering and combating the financing of terrorism. Powerful drug cartels, resorting to extreme violence, have extended their activities across various parts of the country, and these activities pose significant challenges to the government. This situation reflects the magnitude of financial and economic resources and power at the disposal of drug cartels and organized crime. The authorities have taken a number of measures to counter the significant money laundering risks connected with drug trafficking, organized crime, and related offenses.